ENTAL HEALTH NURSING CARE MANAGEMENT FOR MR. M WITH LOW SELF-ESTEEM AT PROF. DR. MUHAMMAD ILDREM MENTAL HOSPITAL, MEDAN, NORTH SUMATRA PROVINCE - Jernita Manullang; Siti Nurmawan Sinaga; Hari Wiyatmini; Lenny Saragih; Yossi Oktaria Saragih; Rahmat Rafli; Desi D. Siburian, (Mitra Husada Health Internasional Conference (MIHHICo), 2025)
Background: Schizophrenia is a severe mental disorder that impairs brain functions, including cognition, emotion, and behavior. It is categorized by positive symptoms (delusions and hallucinations), negative symptoms (social withdrawal and flattened affect), and cognitive deficits (impaired memory and concentration). Although it affects approximately 24 million people worldwide (0.32% of the population), the National Institute of Mental Health (NIMH) ranks it among the top 15 leading causes of disability globally. In Indonesia, the 2023 Indonesian Health Survey highlights significant regional variation: the Special Region of Yogyakarta (DIY) has a prevalence of 9.3%, whereas North Sumatra ranks 21st nationwide at 6.3%. Problem: Initial 2024 data at Prof. Dr. Muhammad Ildrem Mental Hospital indicated that 5% of patients presenting with low self-esteem were diagnosed with schizophrenia-related conditions. This underscores a significant correlation between negative self-perception and the exacerbation of severe psychotic disorders. Objective: The primary aim of this study is to implement comprehensive mental health nursing care management for Mr. M, a patient suffering from low self-esteem, at Prof. Dr. Muhammad Ildrem Mental Hospital in Medan, North Sumatra, in 2025.